Validating and Estimating Indirect Accident Costs in Saudi Construction: A Bottom-Up Approach - Alotaibi, Abdulaziz; Tamrin, Shamsul Bahri Hj. Mohd; Guan, Ng Yee; Hassanain, Mohammad (Advances in Social Sciences Research Journal, 2025)
Accurately estimating the indirect costs of construction accidents is essential to fully understand their economic and social impacts, especially in Saudi Arabia’s rapidly growing construction sector. While direct costs like medical expenses are documented, indirect costs-including lost productivity, project delays, and training-often surpass direct costs but remain difficult to quantify. This study aimed to develop and validate a bottom-up framework to estimate indirect costs of construction accidents across diverse company sizes and project types in Saudi Arabia’s Eastern Province. A quantitative explanatory study was conducted from November 2020 to December 2022 involving 40 construction companies selected via quota sampling to represent various sizes and project types. Indirect cost indicators were identified based on Haupt and Pillay’s framework and validated by an expert panel using the Content Validity Index (CVI) and Kappa statistics. Data on overtime, supervisory time, investigation, training, equipment damage, legal/administrative, and miscellaneous costs were collected through structured questionnaires. Descriptive statistics analyzed cost variations by company size. All nine indirect cost indicators showed strong content validity with CVI scores of 0.8 to 1.0 and substantial expert agreement. Survey results revealed significant differences in indirect costs by company size. Medium-sized firms (101–500 employees) incurred the highest overtime and investigation costs, while large firms (>500 employees) exhibited the greatest supervisory, training, and legal expenses. Smaller firms (<50 employees) faced relatively higher equipment damage and miscellaneous costs. Geographic and project type diversity ensured comprehensive regional representation. The validated framework effectively captures the multifaceted indirect costs of construction accidents in Saudi Arabia. Findings highlight the need for size-specific safety interventions and resource allocation to reduce financial burdens. Tailored prevention strategies and enhanced training programs are crucial, particularly for medium and large companies, while smaller firms require targeted support to manage indirect cost challenges. This study provides a robust foundation for policymakers and industry leaders to improve occupational health and safety investments in the construction sector.